Impact of external knowledge acquisition strategies on innovation: A comparative study based on Dutch and Swiss panel data - Spyridon Arvanitis; Boris Lokshin; Pierre Mohnen; Martin Wörter (ETH Zurich, KOF Swiss Economic Institute, 2013)
There is growing evidence that firms increasingly adopt open innovation practices. In this paper we investigate the impact of two such external knowledge acquisition strategies, buy and cooperate, on firm's product innovation performance. Taking a direct (productivity) approach, we test for complementarity effects in the simultaneous use of the two strategies, and in the intensity of their use. Our results based on large panels of Dutch and Swiss innovating firms, suggest that while both buy and cooperate have a positive effect on innovation, there is little statistical evidence that using them simultaneously leads to higher innovation performance. Results from the Dutch sample provide some indication, that there are positive economies of scope in doing external and cooperative R&D simultaneously conditional on doing internal R&D.
Keywords: O31; O32; 330; Open innovation; R&D collaboration; make; buy strategies; Innovationsmanagement; Wissenstransfer; Unternehmenskooperation; Forschungskooperation; Panel; Schweiz; Niederlande